2020
DOI: 10.3390/ijms21114110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Material and Surface on Mode and Strength of Cell/Matrix Attachment of Human Adipose Derived Stromal Cell

Abstract: A fundamental step for cell growth and differentiation is the cell adhesion. The purpose of this study was to determine the adhesion of different cell lineages, adipose derived stromal cells, osteoblasts, and gingival fibroblast to titanium and zirconia dental implants with different surface treatments. Primary cells were cultured on smooth/polished surfaces (titanium with a smooth surface texture (Ti-PT) and machined zirconia (ZrO2-M)) and on rough surfaces (titanium with a rough surface texture (Ti-SLA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…As some cells remained attached to the implants after removing the implants from the oral mucosa models, it can be interpreted that the bond between the cells and implant surfaces were stronger than the bond between the cells within the oral mucosal model. In line with our findings, Jung et al [ 44 ] recently evaluated the adhesion of different cell lines, including gingival fibroblasts and osteoblasts, to different titanium and zirconia implant surfaces. They showed that the surface texture of the implants significantly affected the cell morphology and cytoskeleton.…”
Section: Discussionsupporting
confidence: 90%
“…As some cells remained attached to the implants after removing the implants from the oral mucosa models, it can be interpreted that the bond between the cells and implant surfaces were stronger than the bond between the cells within the oral mucosal model. In line with our findings, Jung et al [ 44 ] recently evaluated the adhesion of different cell lines, including gingival fibroblasts and osteoblasts, to different titanium and zirconia implant surfaces. They showed that the surface texture of the implants significantly affected the cell morphology and cytoskeleton.…”
Section: Discussionsupporting
confidence: 90%
“…Vinculin and actin play an important role in cell-cell and cell-matrix adhesion. Both are an important component of focal adhesion, which is critical for tissue remodeling, cell migration and other homeostatic processes [39][40][41][42]. Our immunofluorescence experiments revealed that on MD the HGF-1 cells had a spindle-shaped morphology and were aligned along the grooves.…”
Section: Discussionmentioning
confidence: 74%
“…Cells adhere to the ECM via an integrin-mediated adhesion that connects ECM to the cytoskeleton, and integrins serve as receptors for ECM proteins [ 45 ]. In order to ameliorate the regeneration, it is essential to evaluate the cell binding strength to the implant material surface [ 46 ]. In particular, some expressed proteins are vital for the osteogenesis process, RUNX2 is essential and required for physiologic bone formation, osteopontin is a protein involved in normal calcifications and SPARC is one of the most abundant non-collagenous proteins expressed in the mineralized tissues [ 47 ].…”
Section: Discussionmentioning
confidence: 99%